2016
DOI: 10.1177/0829573516648946
|View full text |Cite
|
Sign up to set email alerts
|

Temperamental Differences and Classroom Incivility: Exploring the Role of Individual Differences

Abstract: Incivility involves rude, discourteous, and disrespectful attitudes and behaviours. The present study examined how various temperament traits were related to beliefs of classroom incivility among adolescents. The sample comprised of 222 adolescents (120 boys) between the ages of 12 and 17 (M age = 14.07, SD = 1.54) who were recruited from various extracurricular clubs and sports teams in Southern Ontario. Both intentional and unintentional incivility were examined through separate hierarchical multiple regress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 48 publications
(89 reference statements)
0
11
0
Order By: Relevance
“…Lastly, since this was the first study to explore classroom incivility and social network position, we chose to focus on overall classroom incivility. However, previous research has examined subtypes of classroom incivility based on intentionality (Farrell et al, 2016;Spadafora et al, 2016Spadafora et al, , 2020; thus, future studies should examine whether there might be differences in the association with social network position in relation to these subtypes of classroom incivility. Future studies could also investigate observer-reported classroom incivility.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…Lastly, since this was the first study to explore classroom incivility and social network position, we chose to focus on overall classroom incivility. However, previous research has examined subtypes of classroom incivility based on intentionality (Farrell et al, 2016;Spadafora et al, 2016Spadafora et al, , 2020; thus, future studies should examine whether there might be differences in the association with social network position in relation to these subtypes of classroom incivility. Future studies could also investigate observer-reported classroom incivility.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…In this context, more specifically, we refer to a duality of the role of civility, in that a lack of civility may hamper bullying research, but a lack of civility may also serve to embolden adolescents toward abusing their power in the form of bullying (Marini, 2009). This lack of civility appears to increase with age from early to mid-adolescence (Spadafora, Farrell, Provenzano, Marini, & Volk, 2018), possibly because of a combination of an increased desire for reward seeking along with a diminished capacity for self-control (Steinberg, 2008). In particular, an arrogant lack of cooperativeness may allow individuals to both ignore social civility conventions and exploit social power.…”
Section: Journal Of Childhood Studies Articles From Researchmentioning
confidence: 99%
“…This may help explain the recent success of an anti-bullying program that focuses on working with, rather than against, adolescents' desire for social power. Adolescents appear to be keenly aware of the potential dynamics associated with social power, its acquisition, and its role in the peer group (Cillessen & Rose, 2005;Spadafora, Farrell, et al, 2018). So interventions that try to go against these norms (e.g., relying on unpopular children to change the behaviour of popular children) tend to fail (Garandeau, Lee, & Salmivalli, 2014).…”
Section: Civility Bullying and Transdisciplinary Solutionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Adolescents is a period when personality and neurological tendencies may predispose individuals towards engaging in behavior that lacks consideration for others (Ashton &Lee, 2016 andVolk, 2016). The rise of uncivil behaviors in educational settings may be a reflection of a much larger problem concerning the decline of courteous and polite behaviors and interactions between people in society (Moore, 2012).…”
Section: Introductionmentioning
confidence: 99%